Penerapan Gaya Kepemimpinan Transformasional dalam Meningkatkan Kinerja Karyawan di KSPPS NU Sejahtera: Studi Deskriptif - Isma Wardiana; Budi Sukardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the application of transformational leadership and its contribution to improving employee performance at KSPPS NU Sejahtera. The study employed a qualitative approach with a descriptive approach, conducted through in-depth interviews, non-participatory observation, and documentation of managers and marketing staff. The results indicate that the four dimensions of transformational leadership according to Bass and Avolio idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration have been consistently applied in this cooperative's work environment. Despite challenges during the leadership transition in 2022, the new leaders successfully established open communication, clearly communicated the organization's vision, and demonstrated concern for employees. Consequently, employee morale and performance have improved, reflected in indicators of quality, quantity, resilience, and work attitude. Institutionally, this is demonstrated by the cooperative's revenue growth, reaching IDR 860 billion in 2024, network expansion, and strategic partnerships with national and international institutions. These findings reinforce the relevance of transformational leadership as an effective managerial strategy for improving the performance and sustainability of Sharia-compliant organizations.